Phenomenological Consequences of Girls Witnessing Parental Infidelity - Jamshidi kia , Arezoo; Honarparvaran , Nazanin (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The objective of this study was to explore and determine the phenomenological consequences experienced by adolescent girls who have witnessed parental infidelity. Methods and Materials: This qualitative study employed a grounded theory approach to capture the lived experiences of adolescent girls aged 14–20 years who had directly or indirectly observed parental infidelity. The participants were recruited through purposive sampling from family counseling centers in Shiraz, Iran. Semi-structured, in-depth interviews were conducted with ten participants until data saturation was achieved. Interview protocols were validated by experts in psychology, and interviews were transcribed and analyzed using Strauss and Corbin’s three-phase coding procedure: open, axial, and selective coding. Strategies to ensure trustworthiness included prolonged engagement, member checking, peer debriefing, and maintaining a full audit trail of coding decisions and analytical memos. Findings: Analysis revealed four major categories that represent the core phenomenological consequences of parental infidelity for adolescent girls. First, persistent psychological damages were observed, including depression, anxiety, insomnia, nervous breakdown, and obsessive tendencies in decision-making. Second, a collapse of interpersonal trust emerged, characterized by distrust toward parents, men, love, and fear of marriage. Third, changes in the mental image of family were identified, involving denial of the unfaithful parent, collapse of parental authority, and feelings of helplessness. Finally, despite the trauma, some participants reported psychological and spiritual growth, including cognitive restructuring, heightened awareness of commitment, and positive outcomes from therapeutic experiences. Conclusion: The study highlights that parental infidelity has profound and multifaceted consequences for adolescent girls, encompassing psychological distress, relational insecurity, and identity disruption, yet also carrying the potential for resilience and growth. These findings underscore the need for targeted counseling interventions, culturally sensitive therapeutic support, and preventive education to address the long-term impacts of parental betrayal on adolescents.